Beiträge zur Insekten-Fauna der DDR: Lepidoptera - Tineidae. - Petersen, Günther (Contributions to Entomology = Beiträge zur Entomologie, 1969)
The Tineids (True Moths) are represented in the GDR by 47 species, but only 22 of them are frequently found (including 14 species infesting stored food products and other material of economic importance). Based on an intimate study of literature and a revision of all collections available their distribution on the territory of the GDR as like as dates on life history and food specialization are listed. There are presented keys for the identification of the species together with an additional one restricted to the injurious moths and their larvae, the use of which is facilitated by a total of 205 figures of larval chaetotaxy and genitalia as like as coloured illustrations of the right forewings of 44 species.